(untitled) (translation. a transdisciplinary journal, 2022)
I have real reservations about pushing translation studies in the direction of linguistic ecology even if this new direction offers potentially rich possibilities for interdisciplinary work between comparative literature and area studies. More worries are grounded in the concern that a translation studies overly indebted to linguistic ecology risks fetishizing heritage language as it devotes itself to curatorial salvage: exoticizing burrs, calques and idiomatic expressions as so many ornaments of linguistic local color, reinforcing linguistic cultural essentialism, and subjecting the natural flux and variation of dialect to a standard language model of grammatical fixity.